Is Less Surgical Treatment Possible in the Treatment of Degenerative Spine Diseases? Four-Year Follow-up Results of Foraminal Epidural and Facet Joint Injection Treatments - Yunus Kaçar; Derya Karaoğlu Gündoğdu (Genel Tıp Dergisi)
Aim The study aims to examine the long-term outcomes of foraminal epidural injection and facet joint injection therapies in patients over the age of 60 who have been recommended for surgical intervention for degenerative spinal diseases but have declined surgical treatment due to comorbidities, anesthesia risks, and surgical risks. Methods Between 2018-2019, patients over the age of 60 diagnosed with Degenerative Spinal Disease who declined the recommended surgical treatment and underwent foraminal epidural and facet joint injection therapies were retrospectively evaluated. Patients were assessed using the visual pain scale and MacNab classifications during an average follow-up period of 57.14 (45-68) months. Inclusion criteria for the study included patients being continuously followed up and treated at the same center, regularly attending check-up examinations, and not having emergency surgical indications. Results The study included 35 patients with an average follow-up period of 57.14 months. Patients were treated with either facet joint or foraminal epidural injections in a single session based on their symptoms and complaints. The most striking result of our study is that the visual pain scale and MacNab classification outcomes after spinal injection therapy can be used as indicators for long-term results. Conclusion Sharing the outcomes of commonly practiced spinal injection therapies in the literature more frequently will provide guidance for the treatment planning of challenging conditions, especially like degenerative spinal disease.